Alteration of Neurotrophic Factors After Transplantation of Bone Marrow Derived Lin‐ve Stem Cell in NMDA‐Induced Mouse Model of Retinal Degeneration. Issue 7 (11th January 2017) - Jindal, Neeru; Banik, Avijit; Prabhakar, Sudesh; Vaiphie, Kim; Anand, Akshay
ABSTRACT: Retinal ganglion cell layer (RGCs) is one of the important layers of retina, depleted in Glaucoma. Loss of RGC neurons is a major cellular mechanism involved in its pathogenesis resulting in severe vision loss. Stem cell therapy has emerged as a potential strategy to arrest the apoptotic loss of RGCs and also replace the degenerative cells in damaged retina. Here, we have investigated the incorporation and survival of mouse bone marrow derived Lin‐ve stem cells in N‐methyl‐d ‐aspartate (NMDA)‐induced mouse model of retinal degeneration. Two days after intravitreal injection of NMDA (100 mM) showed significant decrease in ganglion cell number and increase in TUNEL positive apoptotic cells in retinal layers. The injury was further characterized by immunohistochemical expression of Brn3b, GFAP, Bcl2, pCREB, CNTF, GDNF, and BDNF in retinal layers. Lin‐ve cells (100, 000 dose) were intravitreally transplanted after 2 days of injury and evaluated after 7, 14, and 21 days of transplantation. Transplanted cells were found to have migrated from intravitreal space and incorporated into injured retina at 7, 14, and 21 days post‐transplantation. At 21 days Brn3b, CNTF, and BDNF expression was found to be upregulated whereas GDNF was downregulated when compared to respective injury time points. Molecular data showed decrease in the expression of Brn3b, BDNF, CNTF, and GDNF post transplantation when compared with injury groups. This study reveals that Lin‐ve stem cells may exert neuroprotective effect in damaged retina mediated by participation of neurotrophic factors induced by stem cell transplantation at the site of injury. J. Cell. Biochem. 118: 1699–1711, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Our study reveals that Lin‐ve stem cells may exert neuroprotective effect in damaged retina mediated by participation of neurotrophic factors induced by stem cell transplantation at the site of injury.